Art and social justice the media connection - Hajimichael, Michael (Newcastle upon Tyne, UK Cambridge Scholars Publishing, 2015)
"This book is a collection of articles that reflect on various connectivities between art and social justice and media which are pertinent to studying contemporary societies. How different forms of media and art, in the broadest possible meaning of these terms, reflect on, relate to, and campaign for social justice is an important topic to consider as artists, academics and activists." -- Provided by publisher
Introduction Mike Hajimichael -- 1. Ethics and justice in art works Manzu Islam -- 2. Digital media and youth civic practices: strategies to foster online participation Tao Papaioannou -- Transcending cultural identity ascription: agency, social justice, and micro blogging in Brazil Alice Araujo -- Stimulating social sensitivity: Manos Hadjidakis' radio third program in Greece Dimitris Papanikolau -- Art, human rights and social justice Jan Jordaan -- Dialectics and the new media: why ideology still Nikolas Defteras -- The communication of empathy through art: implications for conflict resolution and social justice Andreas Anastasiou -- Down the rabbit hole - up the Maelstrom: shaping the digital landscape to change contemporary art Anton Dragan Maslic -- Socially engaged art and segregated urban contexts: Nicosia experiments Evanthia Tselika -- "Xenitia": living away from home... Always a stranger... Even in a far away land... Mike Hajimichael
Includes bibliographical references
Keywords: Arts and society; Mass media and art; Social justice in art